(untitled) (gjstudies, 2017)
This research investigates the relationship between public sector transparency initiatives and measurable improvements in financial accountability, proposing a novelmethodological framework that diverges from conventional econometric approaches.While existing literature predominantly examines transparency through budgetarydisclosure or anti-corruption indices, this study introduces a multi-dimensional transparency construct integrating procedural visibility, participatory access, and algorithmic auditability of financial data flows. We develop and apply a hybrid evaluationmodel combining qualitative comparative analysis (QCA) with social network analysisof disclosure ecosystems across 42 municipal governments over a ten-year period. Ourmethodology uniquely captures not only the presence of transparency mechanisms buttheir structural integration into accountability feedback loops, including citizen oversight committees, real-time expenditure tracking platforms, and automated anomalydetection systems. The findings reveal a non-linear, threshold-dependent relationship where transparency initiatives trigger significant accountability improvements onlywhen coupled with institutionalized response mechanisms and independent verificationcapacities. Specifically, we identify a transparency-accountability efficacy thresholdbeyond which marginal transparency gains produce diminishing returns, suggesting anoptimal transparency design point. Furthermore, the research uncovers the previouslyundocumented role of ’transparency intermediaries’—civil society organizations andmedia entities that translate raw disclosure into actionable accountability—as criticalmoderating variables. The study contributes original theoretical insights by reconceptualizing transparency not as a static institutional characteristic but as a dynamicprocess of information curation and response, with significant implications for the design of next-generation open government initiatives that move beyond mere disclosuretoward enforceable accountability.